Coronary artery calcium as a predictor of coronary heart disease, cardiovascular disease, and all-cause mortality in Asian-Americans: The Coronary Artery Calcium Consortium. Issue 8 (December 2019) - Orimoloye, Olusola A.; Banga, Sandeep; Dardari, Zeina A.; Uddin, S. M. Iftekhar; Budoff, Matthew J.; Berman, Daniel S.; Rozanski, Alan; Shaw, Leslee J.; Rumberger, John A.; Nasir, Khurram; Miedema, Michael D.; Blumenthal, Roger S.; et al.
Abstract : Background: Coronary artery calcium (CAC) has been shown in multiple populations to predict atherosclerotic cardiovascular disease. However, its predictive value in Asian-Americans is poorly described. Patients and methods: We studied 1621 asymptomatic Asian-Americans in the CAC Consortium, a large multicenter retrospective cohort. CAC was modeled in categorical (CAC = 0; CAC = 1–99; CAC = 100–399; CAC ≥ 400) and continuous [ln (CAC + 1)] forms. Participants were followed over a mean follow-up of 12 ± 4 years for coronary heart disease (CHD) death, cardiovascular disease (CVD) death, and all-cause mortality. The predictive value of CAC for individual outcomes was assessed using multivariable-adjusted Cox regression models adjusted for traditional cardiovascular risk factors and reported as hazard ratios (95% confidence interval). Results: The mean (SD) age of the population was 54 (11.2) years and 64% were men. The mean 10-year atherosclerotic cardiovascular disease risk score was 8%. Approximately half had a CAC score of 0, whereas 22.5% had a CAC score of greater than 100. A total of 56 deaths (16 CVD and 8 CHD) were recorded, with no CVD or CHD deaths in the CAC = 0 group. We noted a significantly increased risk of CHD [hazard ratio (HR): 2.6 (1.5–4.3)] and CVD [HR: 2.3 (1.8–2.9)] mortality per unit increase in In (CAC + 1). Compared to those with CAC scores of 0, individuals with CAC scores of at least 400 had over a three-fold increased risk of all-cause mortality [HR: 3.3 (1.3–8.6)]. Conclusion: Although Asian-Americans are a relatively low-risk group, CAC strongly predicts CHD, CVD, and all-cause mortality beyond traditional risk factors. These findings may help address existing knowledge gaps in CVD risk prediction in Asian-Americans. Abstract : Supplemental Digital Content is available in the text.